Exploring intangible drivers that can lead to supplier preferential treatment towards SMEs - Soh, Jun Ghee (2020)
This research focus on understanding the intangible drivers that engage suppliers and promote their choice to treat selected SME customers preferentially. Suppliers are often driven to treat key customers preferentially to maximize the financial returns, and SMEs are deemed “less attractive”, hence often neglected. SMEs face stringent business conditions due to their disadvantaged size and limited access to resources.